Clustering of Rice Production in South Sulawesi of Januari-April 2022 and 2023 Period - Harun Al-Rasyid Ahmad; Siti Aisa Lamane; Muh. Zainal S. (Universitas Muhammadiyah Palembang, 2024)
Most of the Indonesian people consumes rice as a main food. Based on data from Badan Pusat Statistik, rice production in 2023 has reached 31.10 millions of ton, it decreased by 439.24 thousands of ton or 1.39 percent compared to rice production in 2022 which was 31.54 millions of ton. This research aims to clustering rice production in South Sulawesi for the January-April 2022 and 2023 periods and support more effective decisions in managing rice production in each city/district in South Sulawesi. The results of cluster analysis of Rice Production data in South Sulawesi for the January-April 2022 and 2023 periods using 2023 Agricultural Census data in South Sulawesi based on districts/cities produced 2 clusters. Cluster 1 consists of high amounts of rice production for the January-April 2022 and 2023 periods, which are Bone Regency, Sidrap Regency and Wajo Regency, while the other 21 city/districts are included in cluster 2, which consist the cluster for the low amount of rice production for the January-April 2022 and 2023 period.